Contracting in the new economy : using relational contracts to boost trust and collaboration in strategic business relationships /: using relational contracts to boost trust and collaboration in strategic business relationships. (2021) - Frydlinger, David; Vitasek, Kate; Bergman, Jim; Cummins, Tim
No abstract available